GacA reduces virulence and increases competitiveness in planta in the tumorigenic olive pathogen Pseudomonas savastanoi pv. savastanoi - Lavado-Benito, Carla; Murillo, Jesús; Martínez-Gil, Marta; Ramos, Cayo; Rodríguez-Moreno, Luis (Frontiers in Plant Science, 2024)
GacS/GacA is a widely distributed two-component system playing an essential role as a key global regulator, although its characterization in phytopathogenic bacteria has been deeply biased, being intensively studied in pathogens of herbaceous plants but barely investigated in pathogens of woody hosts. P. savastanoi pv. savastanoi (Psv) is characterized by inducing tumours in the stem and branches of olive trees. In this work, the model strain Psv NCPPB 3335 and a mutant derivative with a complete deletion of gene gacA were subjected to RNA-Seq analyses in a minimum medium and a medium mimicking in planta conditions, accompanied by RT-qPCR analyses of selected genes and phenotypic assays. These experiments indicated that GacA participates in the regulation of at least 2152 genes in strain NCPPB 3335, representing 37.9 % of the annotated CDSs. GacA also controls the expression of diverse rsm genes, and modulates diverse phenotypes, including motility and resistance to oxidative stresses. As occurs with other P. syringae pathovars of herbaceous plants, GacA regulates the expression of the type III secretion system and cognate effectors. In addition, GacA also regulates the expression of WHOP genes, specifically encoded in P. syringe strains isolated from woody hosts, and genes for the biosynthesis of phytohormones. A gacA mutant of NCPPB 3335 showed increased virulence, producing large immature tumours with high bacterial populations, but showed a significantly reduced competitiveness in planta. Our results further extend the role of the global regulator GacA in the virulence and fitness of a P. syringae pathogen of woody hosts.